The Effect of Work Stress, Work Conflict, and the Work Environment on Work Spirit in Employees Pratama Tax Service Office (KPP) Binjai - Rosmani Sinaga; Sutaryat Trisnamansyah; Husen Saeful Insan; Waska Warta (UIN Sunan Gunung Djati Bandung, 2018)
Tax Service Office (KPP) of the Directorate General of Taxes (DGT) work unit that provides taxation services to the public, whether registered as Taxpayers (WP) or not, within the scope of the Directorate General of Taxes working area. The problem of this research is whether work stress, work conflict, and work environment affect the morale of employees of the Pratama Binjai Tax Office (KPP). The data collection technique in this study was carried out with a questionnaire by distributing a list of questions to 53 respondents, from the results of the Fcount value of 4489.184 with a significant level of 0.00. Because Fcount 4489.184> Ftable 2.79 and the significant probability is much smaller than 0.05, namely 0.00 <0.05, the regression model can be said that work stress, work conflict, and work environment simultaneously have a positive and significant effect on morale. work. Partial test (t-test) shows that: for the variable work stress, the value of tcount is 4.465 <ttable 1.676 with a significant value of 0.029> 0.05, meaning that partially, the variable of work stress has a positive and significant effect on morale. Work conflict variable value tcount 18.576> ttable 1.676 with a significant 0.000 <0.050, meaning that partially the work conflict variable has a positive and significant effect on morale. Work Environment Variable tcount 19.648> ttable 1.676 with a significant 0.001 <0.050, meaning that partially the Work Environment variable has a positive and significant effect on morale. The determination test is the adjusted R square of 0.996, this means that 99.6% of the variation in morale can be explained by the independent variables of work stress, work conflict, and work environment while the rest (100% - 99.6% = 0.4%) can be explained by other independent variables which not included in this study